INOVASI PENDIDIKAN PANCASILA: MODEL PERMEN DALAM MENINGKATKAN KARAKTER TANGGUNG JAWAB SISWA SD - Yulianti, Dewi; Yogi Prihandoko; Noorhapizah; Darmiyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low levels of student activity, responsibility of character, and learning outcomes in Pancasila Education are the focus of this study. One contributing factor is the use of one-way teaching methods that offer minimal student participation. As a result, students struggle to understand the material and fail to demonstrate responsible behavior during the learning process. This study aims to describe teacher and student activities, analyze responsibility character, and assess student learning outcomes through the PERMEN model. A qualitative approach with Classroom Action Research (CAR) was used over four meetings. The subjects were 14 fourth grade students, consisting of 8 boys and 6 girls. Qualitative data were obtained through observation, and quantitative data came from questionnaires and tests. The results showed consistent improvement from meetings 1 to 4: student activity increased from 29% to 100% (very active), responsibility character rose from 57% to 93% (very responsible), and classical completeness in cognitive, affective, and psychomotor domains improved from 50%, 50%, and 57% to 100%, respectively. The PERMEN model proved effective in enhancing student activity, responsibility character, and learning outcomes. Its application offers an alternative to build interactive learning experiences and foster active student participation.